Slagging of coal blends: comparison between pre-blended and in furnace blend - Abdul Latiff, Abdul Somad; Musa, Mukhtaruddin; Anhar, Zaki; Illias, Suhaimi; Ani, Mohd Hanafi (IOP Publishing Ltd, 2020)
Coal blending technique in electric generating power plant has been widely used to reduce coal consumption cost. However, due to various coals from different places blended together, it had caused problems. Slagging formed during the operations can reduced boiler efficiency, resulting high costs for maintenance caused by blockage, corrosion and erosion. Many empirical indices and predictive method have been developed to minimize these problems but most are unreliable for coals from different places and many predictive methods are carried out in different environment. In this research, the method starts from fabricating the pre-blended and in furnace blend techniques at a local coal pulverized power plant. After feeding the coal blends for coal trial burn, the resulting ash deposition are collected at the burner where slagging usually occurs. The raw coals in used and the slagging samples are then characterized and determine their crystalline phase and compositions by using X-Ray Diffraction (XRD) and Sacnning Electron Microscope Energy Dispersive Xray (SEM/EDX). From XRD analysis, compounds such as quartz, cristobalite low and manganosite were found as main species in ash deposition at all location of collected slagging. However, there are also some compound exist at specific location with specific technique being used. In the burner area for pre blended technique, compound Al2SiO5, Mg2Al4Si5, KNO¬2 and FeO was found, whereas in furnace blend K2Mn¬2(SO4)3 was found. At bottom part of the furnace, pre-blended graphite was presence and in furnace yield MnO¬¬2 and Al2SiO5. At top part where superheater reside, the existence of mullite, Al2(Al2.5Si1.5)9.75 was found for pre-blended technique and microcline, KAlSiO¬3O8 is observed from in furnace blend technique. From the EDX analysis, in furnace technique shows more complete combustion and feasible for less slagging inside the furnace compared to pre-blended technique.